Determinants Affecting The Implementation Of Digitalization To Increase The Income Of Msmes In Kota Pari Village - Rizal Lubis; Ahmad Fadlan; Aji Sadewo (MANAGER: Journal of Management and Administration Science, 2024)
Rapid digitalization has changed the face of business today, posing a challenge to established business models in all sectors of the economy. Digital business strategy is a critical change that must be made to firm skills, operational procedures, and business processes and strategies in order to achieve digital transformation. In the process of MSMEs, digitalization of marketing is inevitable since it will allow marketing to keep up with technological changes. In order to strengthen the local economy and improve family welfare, small businesses are crucial in many regions, including Kota Pari Village in North Sumatra. This type of research used a quantitative descriptive approach. The target population in this study were all MSMEs in Kota Pari village, which amounted to approximately 100 MSMEs. The number of samples taken in this study was 40 MSMEs. Data processing techniques using SPPS version 26. Data analysis was used validity and reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple regression analysis, and hypotheses test. Based on the research results, it was found that the information and technology training variable partially had a positive and significant effect on MSMEs income. The availability of facilities and infrastructure variable partially had a positive and significant effect on MSMEs income. The information and technology training variable and the availability of facilities and infrastructure variable simultaneously had a positive and significant effect on MSMEs income.